The Role of Teachers in Implementing Multicultural Education Values in the Curriculum 2013 Implementation in Indonesia - Suryaman; Juharyanto (International Journal of Educational Studies, 2020)
This study wants to examine the role of teachers in implementing the values of multicultural education in the curriculum 2013 implementation in primary education. The method of this research is descriptive qualitative. Data were collected through observation, interviews, and documentation. The informants in this study were the Principal, Vice Principal for Public Relations, Teachers, Students, and parents. The research showed that the school has a pattern as a multicultural public school. Teachers have a role in integrating multicultural values into the preparation of lesson plans, the application of fun learning, and the accommodation of diversity of students of different religions.